2015
DOI: 10.1002/2015jc010832
|View full text |Cite
|
Sign up to set email alerts
|

The air‐water CO2 exchange of a coastal sea—A sensitivity study on factors that influence the absorption and outgassing of CO2 in the Baltic Sea

Abstract: In this study, the BALTSEM model is used to estimate how air‐water CO2 fluxes in the Baltic Sea respond to parameterizations of organic alkalinity (Aorg), gas transfer, and phytoplankton growth, and further to changes in river loads. The forcing data include the most complete compilation of Baltic river loads for dissolved inorganic and organic carbon (DIC and DOC) and total alkalinity (TA). In addition, we apply the most recent estimates of internal TA generation in the system. Our results clearly demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…However, short-term variability is not always incorporated in modelling studies. Some marine models ignore short-term variability in the atmospheric CO 2 concentration, when the air-sea CO 2 exchange is modelled (Omstedt et al 2009;Gypens et al, 2011;Kuznetsov and Neumann, 2013;Gustafsson et al, 2015;Valsala and Murtugudde, 2015). Similarly, when the air-sea CO 2 exchange is studied from an atmospheric perspective, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, short-term variability is not always incorporated in modelling studies. Some marine models ignore short-term variability in the atmospheric CO 2 concentration, when the air-sea CO 2 exchange is modelled (Omstedt et al 2009;Gypens et al, 2011;Kuznetsov and Neumann, 2013;Gustafsson et al, 2015;Valsala and Murtugudde, 2015). Similarly, when the air-sea CO 2 exchange is studied from an atmospheric perspective, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For that reason we have no estimates of basin-wide mean C concentrations based on observations. Simulated organic and inorganic carbon concentrations have however been validated in earlier publications (Gustafsson et al 2014a(Gustafsson et al , 2015, and average basin-wide simulated concentrations of TC, TOC, and DIC are presented in Table 3.…”
Section: Pools and Ratiosmentioning
confidence: 99%
“…This A org contribution amounted from 1.5 to 3.5 % of the measured A T values. Even higher values of more than 50 µmol kg −1 were found by Hammer et al (2017) in the Baltic Sea surface mixed layer during the spring phytoplankton bloom. They reported also that A org decreases with depth and approaches 0 below the permanent halocline due to pH decrease.…”
Section: Effect Of Organic Alkalinitymentioning
confidence: 84%
“…According to the definition (Dickson, 1981), they should be considered strong acids. In experimental studies Hammer et al (2017) also found that humic and/or fulvic substances are more acidic than the bulk DOM naturally occurring in the Baltic Sea. This may also be a source of uncertainty in the A T measurements as the determination of the titration end-point requires the titration of the samples through this pH region.…”
Section: Effect Of Organic Alkalinitymentioning
confidence: 90%
See 1 more Smart Citation